2006
DOI: 10.1111/j.1527-3466.2006.00204.x
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Studies with Adrenomedullin and Its Binding Protein as Cardiovascular Protective Agents for Hemorrhagic Shock

Abstract: Traumatic injury is a major, largely unrecognized public health problem in the US that cuts across race, gender, age, and economic boundaries. The resulting loss of productive life years exceeds that of any other disease, with societal costs of $469 billion annually. Most trauma deaths result either from insufficient tissue perfusion due to excessive blood loss, or the development of inflammation, infection, and vital organ damage following resuscitation. Clinical management of hemorrhagic shock relies on mass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 28 publications
(31 reference statements)
0
8
0
Order By: Relevance
“…Finally, a study on RAMP1 knockout mice suggested that CGRP might produce both pro-and anti-inflammatory effects (Tsujikawa et al, 2007). Adrenomedullin is reported to exert pro-inflammatory roles (Clementi et al, 2000; Wong et al, 2005; Ma et al, 2006), but there is growing evidence of its protective anti-inflammatory roles in experimental models of diseases, such as pulmonary injury, hemorrhagic or septic shock, colitis, ischemia–reperfusion or arthritis (von der Hardt et al, 2002; Ashizuka et al, 2005; Cui et al, 2005; Wu and Wang, 2006; Carrizo et al, 2007; Dackor and Caron, 2007; Gonzalez-Rey et al, 2007). The emerging picture indicates that CGRP and adrenomedullin can exert either pro-inflammatory effect or anti-inflammatory effect in a highly regulated tissue-specific and stimulus-specific manner.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, a study on RAMP1 knockout mice suggested that CGRP might produce both pro-and anti-inflammatory effects (Tsujikawa et al, 2007). Adrenomedullin is reported to exert pro-inflammatory roles (Clementi et al, 2000; Wong et al, 2005; Ma et al, 2006), but there is growing evidence of its protective anti-inflammatory roles in experimental models of diseases, such as pulmonary injury, hemorrhagic or septic shock, colitis, ischemia–reperfusion or arthritis (von der Hardt et al, 2002; Ashizuka et al, 2005; Cui et al, 2005; Wu and Wang, 2006; Carrizo et al, 2007; Dackor and Caron, 2007; Gonzalez-Rey et al, 2007). The emerging picture indicates that CGRP and adrenomedullin can exert either pro-inflammatory effect or anti-inflammatory effect in a highly regulated tissue-specific and stimulus-specific manner.…”
Section: Introductionmentioning
confidence: 99%
“…However, after comparing with our published studies [6,36], human AM/human AMBP-1 is as effective as rat AM/human AMBP-1 after hemorrhage and resuscitation in rats. The doses and ratio of human AM and human AMBP-1 used in this study were chosen based on our previous studies using rat AM and human AMBP-1 [6,[35][36][37][38]. We will conduct additional efficacy studies in the future to determine the optimal protective dosage and ratio of human AM/AMBP-1 after hemorrhage and resuscitation.…”
Section: Discussionmentioning
confidence: 99%
“…pGz induces pulsatile shear stress to the vascular endothelium and has also been shown to increase eNO and eNOS in several animal species and humans [2,3,[5][6][7][8][56][57][58][59], which are in large part the basis for the observed survival, decreased oxygen consumption, and better regional microvascular blood flow during hemorrhage observed in the present study.…”
Section: Hr (Bpm)mentioning
confidence: 93%
“…Vascular responsiveness to the vasodilator peptide adrenomedullin (AM) is depressed after severe blood loss due to down-regulation of the AM binding protein-1, and administration of AM and its binding protein-1 to rats after hemorrhage reduced hemorrhageinduced mortality [59]. pGz increases AM in pigs [60] and, therefore, may also contribute to the effects of pGz.…”
Section: Hr (Bpm)mentioning
confidence: 99%